Constructing heroism: submarines, submariners and the Dardanelles Campaign, 1915. (3rd July 2018) - Rowe, Laura
ABSTRACT: This article explores how the Royal Navy, in light of its highly ambiguous relationship with the submarine, was able to negotiate the image of their own submarines and submariners into their existing concepts of 'the best traditions and customs of the service'. It will consider how British submariners viewed themselves, how the surface fleet felt towards this new breed of naval men, and how their actions were constructed in a public sphere. This article will consider the various constructions of the heroic narratives surrounding campaign and will explore how and why these various narratives were constructed and reconstructed as they were, and what impact 'heroism' had on the prosecution of the campaign itself.